The Effect of Arable Land Management on the Reaction of Anaerobic Ammonium Oxidation (Anammox): A Meta-Analysis - Qiannan Yang; Lingxuan Gong; Xiaolei Zhang; Guilong Zhang; Lili Wang (Agronomy)
Soil anaerobic ammonium oxidation (anammox) can eliminate reactive nitrogen (N) without generating nitrous oxide and is a key factor in N loss in agricultural ecosystems. Nevertheless, it remains unclear what determines the anammox rate and hzs gene abundance under various cropland management. This study synthesized 100 observations to elucidate the effects of cropland management (including biochar, manure, straw amendment, and N fertilization) on the anammox rate and hzs gene abundance and the governing factors of anammox processes from cropland systems. Our meta-analysis revealed that biochar addition significantly increased the anammox rate by 415%, while manure and N fertilization enhanced the anammox rate by 107% and 60%, respectively. The hzs gene abundance was increased by 240% and 68% under biochar amendment and N fertilization, respectively. Furthermore, biochar increased the anammox rate during the long-term duration (>10 years) at low N application rates and enhanced hzs gene abundance in acidic soil due to increased soil pH. For manure amendment and N fertilization, the anammox rate was significantly promoted in warm, wet climates with lower C/N and higher NH4+-N content. The hzs gene abundance was enhanced in wetter environments (high MAP and aridity index) combined with higher NH4+-N content. This study highlights that alkaline, humid, warm environments, lower C/N, and higher NH4+-N play important roles in determining anammox rate and related bacterial activity. This study provides a new insight into understanding and potentially managing the effects of anammox in cropland cultivation.